Effects of multidimensional life management on healthy behavior in polycystic ovary syndrome patients: A randomized controlled trial - Guo, Yunmei; Liu, Ying; Yan, Xin; Ding, Rui; Wang, LianHong (Frontiers in Psychology, 2022)
Objective: To confirm the effects of a trans-theoretical model based on multidimensional life management on healthy behavior in patients with polycystic ovary syndrome (PCOS). Methods: Eighty eligible patients were recruited from March 2021 to June 2021 and randomly assigned to either the intervention (n=40) or control (n=40) groups. Outcome measures include health-promoting behavior, self-efficacy, anthropometrics, and number of unplanned outpatient admissions. Data were collected at baseline, 3 months and 6 months after intervention. The chi-square test, rank-sum test, t-test, and repeated measurement analysis of variance were used to analyze the data. Results: Sixty-six participants completed the study: 35 participants in the intervention group and 31 in the control group. After 6 months of intervention, the healthy behavior level of patients with PCOS increased from moderate (health promoting lifestyle profile (HPLP)-II score 105.37 ± 12.57) to good (156.94 ± 19.36) in the intervention group; no change was observed in the control group. In addition, the total self-efficacy score (P<0.001), PCOS-related unplanned outpatient admissions (P=0.008), waist circumstance (P=0.016), and body mass index (P=0.011) were found to have a significant difference in the intervention group at 6 months. Meanwhile, repeated measures analysis of variance showed a significantly greater improvement in health-promoting behavior and self-efficacy over time in the intervention group than in the control group (P<0.001). Conclusion: The trans-theoretical model based on multidimensional life management positively affected healthy behavior, self-efficacy, number of unplanned outpatient admissions, and anthropometrics in patients with PCOS.